2017
DOI: 10.1055/s-0043-111898
|View full text |Cite
|
Sign up to set email alerts
|

Apple Pomace as Potential Source of Natural Active Compounds

Abstract: Apple pomace is a waste product of the apple manufacturing industry that has been in the focus of life sciences as it represents a low-cost source of fruit-derived compounds. High fruit consumption is associated with beneficial health effects, and therefore, apple pomace and its constituents raise therapeutic interest. The present work reviews (i) the chemical constituents of apple pomace, (ii) optimized extraction methods of apple pomace compounds, and (iii) biological activities of apple pomace. Current evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 135 publications
5
77
1
Order By: Relevance
“…The optimal temperature for the water extraction process is from 85 to 95°C (Candrawinata et al 2014). Waldbauer in a review noted that water extraction using a combination of 100°C water temperature, 37 min extraction time, and 100 ml/g solvent to solid ratio provided an opportunity to extract the antioxidants of apple pomace by limiting the formation of 5-hydroxymethylfurfural (Waldbauer et al, 2017). Under hot water extraction conditions, the cellular structure of plant tissues can be disrupted, releasing compounds of interest, which then may dissolve in the liquid water (Plaza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal temperature for the water extraction process is from 85 to 95°C (Candrawinata et al 2014). Waldbauer in a review noted that water extraction using a combination of 100°C water temperature, 37 min extraction time, and 100 ml/g solvent to solid ratio provided an opportunity to extract the antioxidants of apple pomace by limiting the formation of 5-hydroxymethylfurfural (Waldbauer et al, 2017). Under hot water extraction conditions, the cellular structure of plant tissues can be disrupted, releasing compounds of interest, which then may dissolve in the liquid water (Plaza et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Apple pomace is a promising source of different functionally important bioactive compounds: carbohydrates, proteins, fatty acids, phenolic compounds, vitamins, minerals and others, with a wide range of food applications. Moreover, apple pomace can be widely used for obtaining several bioactive compounds (García et al, 2009;Kalinowska et al, 2014;Rabetafika et al 2014;Ajila et al, 2015;Perussello et al 2017;Waldbauer et al, 2017). Preclinical studies have found that apple pomace and its isolated extracts improved lipid metabolism, antioxidant status and gastrointestinal function, and had a positive effect on metabolic disorders (e.g., hyperglycemia, insulin resistance, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Apple pomace (AP) is a waste/by‐product produced by apple processing industries, mainly during the juice or cider production . The pomace consists of pulp, skin, seeds, and stalks and accounts about 25% weight of the fresh fruit , representing up to 3.6 million tons of annual production. The large portion of this pomace is dumped as a waste, which has serious environmental implications .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are credited for the various health promoting roles of AP, including antioxidant, antidiabetic, antiproliferative, anti‐inflammatory, antimicrobial, etc. (reviewed in detail in ). Moreover, recent studies have also revealed that AP is positively associated with bioavailability of nutrients , triglycerides, and cholesterol homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Annual global apple juice concentrate production is around 1.1 million tones per year which gives the value of over 1.6 million tones of wastes Agriculture & Farming, Food & Beverage, World (2015). In Poland their amount reaches the value of 0.3 million tones every year (Kołodziejczyk, Markowski, Kosmala, Krol, & Plochrski, 2001). These residues, commonly known as apple pomace, account for approximately 25%-30% of the weight of the original fresh fruit (Gullon, Falque, Alonso, & Parajo, 2007).…”
mentioning
confidence: 99%